Counseling on healthy snack and food for balanced nutrition achievement - Esthy Rahman Asih; Yuliana Arsil (Poltekkes Kemenkes Yogyakarta, 2021)
Healthy food is an essential part of the process of growth and development of children, as well as the basis for maintaining health. In line with the times, more and more chemicals are used as additives and the misuse of harmful chemicals in food can cause disease. The purpose of this activity is to increase the knowledge of mothers in choosing healthy snacks and being able to provide healthy provisions for children at school. This community service activity was carried out in Pematang Kapau Village which was attended by 16 women. This community service is carried out using the Focus Group Discussion (FGD) method, pre-test, and post-test, counseling, the practice of identifying dyes with the acid-base concept, processing practices, practice evaluation, and advocacy. The results of this community service show that the knowledge of respondents before and after counseling is good, with an average of 73.75 % and after counseling, there is an increase in the average knowledge of respondents by 95.31 %. The attitude of the respondents before and after the counseling was of good value, the score before the counseling was 82.50 %, and after the counseling was 98.13 %. The behavior of the respondents before and after counseling was in the category of positive behavior, the behavioral score before counseling was 82.50%, and after counseling was 98.13%. Some of the respondents have prepared lunches or healthy snacks to take their children to school so that children do not snack randomly.